Industrial Need Analysis in Bakery to Develop Bakepreneurship Learning Model - Muhammad Husin Syarbini; Budi Santosa; Muhammad Sayuti (Journal of Vocational Education Studies, 2020)
Vocational education has an important role in preparing students to have the skills needed by the industry. This study aims to analyze the needs of the bakery industry to develop a learning model of Bakepreneurship. This study using descriptive qualitative approach by analyzing the needs in the aspect of 1) student, 2) teacher, 3) curriculum, and 4) industry. Based on the analysis results of the stakeholders, we found an idea to develop a Bakepreneurship learning model that can be used as a reference in pastry and bakery learning in the vocational school. Bakepreneurship learning model is a learning model that combines comprehensively aspects of soft skills, hard skills, and entrepreneurship that aim to equip students with the competencies needed by the bakery industry.